2021
DOI: 10.3389/fpls.2021.706567
|View full text |Cite
|
Sign up to set email alerts
|

Night-Warming Priming at the Vegetative Stage Alleviates Damage to the Flag Leaf Caused by Post-anthesis Warming in Winter Wheat (Triticum aestivum L.)

Abstract: The asymmetric warming in diurnal and seasonal temperature patterns plays an important role in crop distribution and productivity. Asymmetric warming during the early growth periods of winter wheat profoundly affects its vegetative growth and post-anthesis grain productivity. Field experiments were conducted on winter wheat to explore the impact of night warming treatment in winter (Winter warming treatment, WT) or spring (Spring warming treatment, ST) on the senescence of flag leaves and yield of wheat plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Until recently, it remains unclear whether there are asymmetric impacts of changes in day and night temperatures on marsh vegetation of the Qinghai‐Tibet Plateau. Given the asymmetric increase in global daytime and nighttime temperatures (B. Liu et al., 2004; Fan et al., 2021; Karl et al., 1991; Shen, Liu, et al., 2014; Shen, Zhang, et al., 2014), it is necessary to explore whether the daytime and nighttime temperature changes have a similar effect on marsh NPP on the Qinghai‐Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, it remains unclear whether there are asymmetric impacts of changes in day and night temperatures on marsh vegetation of the Qinghai‐Tibet Plateau. Given the asymmetric increase in global daytime and nighttime temperatures (B. Liu et al., 2004; Fan et al., 2021; Karl et al., 1991; Shen, Liu, et al., 2014; Shen, Zhang, et al., 2014), it is necessary to explore whether the daytime and nighttime temperature changes have a similar effect on marsh NPP on the Qinghai‐Tibet Plateau.…”
Section: Introductionmentioning
confidence: 99%
“…Given the asymmetric increase in global daytime and nighttime temperatures (B. Liu et al, 2004;Fan et al, 2021;Karl et al, 1991;Shen, Liu, et al, 2014;Shen, Zhang, et al, 2014), it is necessary to explore whether the daytime and nighttime temperature changes have a similar effect on marsh NPP on the Qinghai-Tibet Plateau.…”
mentioning
confidence: 99%
“…Fokar et al [57] and Liu et al [58] registered similar slight flag leaf senescence after anthesis in the case of optimal conditions, and this can be accelerated by heat and drought conditions, while [59] affirm that post-anthesis drought substantially accelerated the loss of chlorophyll. In a previous study [60], the authors observed that the chlorophyll content was highly maintained in the early grain-filling period, and their photosynthetic capacity gradually became lower after this period. Regarding the carotenoid content, during the first experimental year (Figure 2C), a high level was maintained from booting to 21 DAA (>65 mg/100 g DM) in flag leaf as a cellular defense mechanism to minimize the damage due to oxidative stress [61].…”
Section: Discussionmentioning
confidence: 90%
“…Drought-tolerant genotypes retained many photosynthetic pigments under drought stress (Epee Misse, 2018). Also, it has been observed that the chlorophyll content was highly maintained during the initial grain-filling period, and their photosynthetic capacity gradually decreased after this period (Fan et al, 2021). The significant relationship between chlorophyll content with resource limitation seems to be due to stronger sinks in these genotypes.…”
Section: Effect Of Drought Stress On the Chlorophyll Content Of Flag ...mentioning
confidence: 91%